Influence of various positive airway pressure levels on catheterization of the right internal jugular vein - Renganathan S; Ramji R; Ganesh Prabhu SC (Asian Journal of Medical Sciences, 2024)
Background: Central venous catheterization is a commonly used method of administering drugs and measuring central venous pressure during major surgery. Chronic obstructive pulmonary disease, acute respiratory distress syndrome, and obstructive sleep apnea are among the respiratory disorders that can be treated with positive airway pressure (PAP). While PAP therapy benefits patients with respiratory disorders, its impact on central venous catheterization must be more adequately studied, particularly in the right internal jugular vein (RTIJV). Aims and Objectives: The study aimed to predict the most applicable PAP for RTIJV catheterization and to evaluate the complications with different airway pressures. Materials and Methods: This study was conducted using a comparative prospective randomized control trial study design in a tertiary care hospital. One hundred participants were selected from subjects who came for gastrointestinal tract surgery and urological surgery, and they were randomized through a computer-generated random number table. Results: Participants were divided into four different groups (A, B, C, and D), and they were subjected to four pressures 0 cmH2O, 10 cmH2O, 15 cmH2O, and 20 cmH2O, respectively. The cross-sectional area of RTIJV is significantly increased in Groups C and D compared to Groups A and B. The number of completed catheterizations was higher in Groups C and D. The number of first-pass punctures was also higher in Groups C and D. Depth of needle insertion is significantly reduced with increased pressure. Conclusion: Moderate-to-high PAPs, specifically around 15 cmH2O to 20 cmH2O, boost catheterization success. This is achieved through improved vein dilation, enhanced accuracy, and decreased needle insertion depth.